2019
DOI: 10.2147/jpr.s213912
|View full text |Cite
|
Sign up to set email alerts
|

<p>Rational treatment of chemotherapy-induced peripheral neuropathy with capsaicin 8% patch: from pain relief towards disease modification</p>

Abstract: Purpose Chemotherapy-induced peripheral neuropathy (CIPN) with associated chronic pain is a common and disabling condition. Current treatments for neuropathic pain in CIPN are largely ineffective, with unfavorable side-effects. The capsaicin 8% patch (capsaicin 179 mg patch) is approved for the treatment of neuropathic pain: a single topical cutaneous application can produce effective pain relief for up to 12 weeks. We assessed the therapeutic potential of capsaicin 8% patch in patients with painf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 83 publications
5
64
0
8
Order By: Relevance
“…The coexistence of sensory fiber loss with neuropathic pain and the capacity of interventions that promote neuroprotection and regeneration of fibers to alleviate indices of pain has also been reported in animals and humans with diabetic peripheral neuropathy (42) and chemotherapy-induced peripheral neuropathy (82,83). A recent study has shown that gut bacteria eradication by a longer antibiotic treatment paradigm prevented development of mechanical hyperalgesia in a model of chemotherapy-induced pain (30).…”
Section: Discussionmentioning
confidence: 95%
“…The coexistence of sensory fiber loss with neuropathic pain and the capacity of interventions that promote neuroprotection and regeneration of fibers to alleviate indices of pain has also been reported in animals and humans with diabetic peripheral neuropathy (42) and chemotherapy-induced peripheral neuropathy (82,83). A recent study has shown that gut bacteria eradication by a longer antibiotic treatment paradigm prevented development of mechanical hyperalgesia in a model of chemotherapy-induced pain (30).…”
Section: Discussionmentioning
confidence: 95%
“…In our study, this assessment allows the pathological confirmation of the behavioral test results, providing them with a strong and reliable support, but it is also important since IENF density measurement is used in the clinical setting, making the translation of the preclinical results much easier and more reliable [ 26 ]. Furthermore, there are examples of clinical treatment effects with pharmacological agents that correlate with the reversal of IENF reduction [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A small non-randomised study of topical menthol in 52 patients showed improved BPI scores 126 , and combination therapy with baclofen, amitriptyline and ketamine showed an improvement on some of the EORTC QLQ-CIPN-20 measures 127 . Topical 8% capsaicin patch application following CIPN has been shown to improve continuous pain, neuropathic pain symptoms, and patient global impression of change 128 . This treatment has also been found to improve IENF density, suggesting underlying disease modification 128 .…”
Section: Treatmentmentioning
confidence: 99%